2018
DOI: 10.1111/bjd.17188
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence rates of cutaneous squamous cell carcinoma of the head and neck after Mohs micrographic surgery vs. standard excision: a retrospective cohort study

Abstract: MMS might be superior to standard excision for cSCCs of the head and neck because of a lower rate of recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(45 citation statements)
references
References 15 publications
(17 reference statements)
0
45
0
Order By: Relevance
“…Other forms such as ‘slow Mohs’ or the ‘Breuninger’ technique can also be considered, but generally take more time than MMS which can lead to a greater burden of treatment. Cure rates of MMS in BCC and cSCC are superior over conventional surgical excision . Previous studies report that MMS is well‐tolerated in elderly patients .…”
Section: Discussionmentioning
confidence: 98%
“…Other forms such as ‘slow Mohs’ or the ‘Breuninger’ technique can also be considered, but generally take more time than MMS which can lead to a greater burden of treatment. Cure rates of MMS in BCC and cSCC are superior over conventional surgical excision . Previous studies report that MMS is well‐tolerated in elderly patients .…”
Section: Discussionmentioning
confidence: 98%
“…MMS is more time-consuming, labor-intensive, and expensive, compared to conventional excision. A retrospective study including 579 patients with 672 cSCCs of the head and neck (380 treated with MMS and 292 with standard excision) reported that MMS could be superior to standard excision for cSCC of the head and neck because of the lower rate of recurrence [152].…”
Section: Micrographically Controlled Surgerymentioning
confidence: 99%
“…Since the metastasis rate of SCC increases to 30.3% after recurrence, and the survival rate after metastasis decreases to 34.4%, the authors recommended Mohs surgery because of the low postoperative recurrence rate 67 . Furthermore, van Lee et al 68 . compared patients who underwent Mohs surgery and those who underwent usual surgery among 672 SCC patients.…”
Section: Process Of Guidelines Developmentmentioning
confidence: 99%